PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI HOTEL GRAND INNA MUARA PADANG - Azwar, Hendri; Chair, Ira Meirina; Abrian, Youmil (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
The research aimed to see the Influence of Work-Discipline towardWorkers’ Performance of Grand Inna Muara Hotel in Padang. The research wasquantitative descriptive by using associative clausal method. The population was130 workers of Grand Inna Muara Hotel. The samples were 98 people who wereobtained by using simple random sampling technique. The instrument that wasused for collecting the data was questionnaire. The questionnaire used Likert scalewhich has qualified validity and reliability. Based on the research, work-disciplineof the workers was categorized as very good (87, 75%), meanwhile workers’performance was categorized as good (68, 36%). The results revealed a positive,significant correlation between work-discipline toward workers’ performance ofGrand Inna Muara Hotel that is about 6, 8%. In other words, Ha is accepted.Keywords: Work-Discipline, and Workers’ Performance